Legal Status of the State Civil Servants in System of Obligatory Social Insurance - Natalia Aleksandrovna Sokolova (Сибирское юридическое обозрение, 2011)
The article analyzes the process of getting insurance by the state civil servants in system of obligatory social insurance under such conditions when legislators attempted to create a special system of social security for this category of citizens.